Formation, and mechanical and magnetic properties of bulk ferromagnetic Fe-Nb-B-Y-(Zr, Co) alloys - Park, JM; Park, JS; Kim, DH; Kim, JH; Fleury, E (CAMBRIDGE UNIV PRESS, 2006)
Fe element was partially substituted by Zr and Co in an attempt to enhance the glass-forming ability, and mechanical and soft magnetic properties of Fe(74-x)Nb(6)B(17)Y(3)(Zr, Co)(x) (x = 3, 5, 8) amorphous alloys. Both partial replacements resulted in the enhancement of the glass-forming ability, and 3-mm diameter rods with a fully amorphous structure were prepared by a copper mold casting method. Zr and Co containing Fe-based bulk amorphous alloys exhibited high compressive fracture strength of about 4 and 3.5 GPa, respectively. However, Zr and Co induced different effects on the magnetic properties. Whereas the partial replacement of Fe by Zr was found to decrease dramatically the saturation magnetization, the partial replacement of Fe by Co provided an increase of about 25% of the saturation magnetization.
Keywords: GLASS-FORMING ABILITY; METALLIC GLASSES; SUPERCOOLED LIQUID; AMORPHOUS-ALLOYS; SUPERHIGH STRENGTH; SYSTEM